2015
DOI: 10.3748/wjg.v21.i47.13212
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound elastography: Current status and future perspectives

Abstract: Elastography is a new ultrasound modality that provides images and measurements related to tissue stiffness. Endoscopic ultrasound (EUS) has played an important role in the diagnosis and management of numerous abdominal and mediastinal diseases. Elastography by means of EUS examination can assess the elasticity of tumors in the proximity of the digestive tract that are hard to reach with conventional transcutaneous ultrasound probes, such as pancreatic masses and mediastinal or abdominal lymph nodes, thus impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 74 publications
0
64
0
6
Order By: Relevance
“…The summary sensitivity was 81% (95% CI: 71-88) and the specificity was 91% (95% CI: [83][84][85][86][87][88][89][90][91][92][93][94][95][96] for the prediction of significant liver fibrosis. Subgroup analysis revealed that 2D-SWE had an excellent diagnostic performance according to each degree of liver fibrosis.…”
Section: Technical Success Rates Of Liver Stiffness Estimatesmentioning
confidence: 99%
See 1 more Smart Citation
“…The summary sensitivity was 81% (95% CI: 71-88) and the specificity was 91% (95% CI: [83][84][85][86][87][88][89][90][91][92][93][94][95][96] for the prediction of significant liver fibrosis. Subgroup analysis revealed that 2D-SWE had an excellent diagnostic performance according to each degree of liver fibrosis.…”
Section: Technical Success Rates Of Liver Stiffness Estimatesmentioning
confidence: 99%
“…Real-time elastography (RTE) has been used mainly for the evaluation of the pancreas [83][84][85][86], the thyroid [87][88][89][90][91][92][93][94], the prostate [95], the breast [5,96] but also for the liver [1,2,7,97]. Published evidence in children is scarce and contradictory [98][99][100].…”
Section: Strain Imaging (Real-time Elastography (Rte))mentioning
confidence: 99%
“…However, EUS-guided biopsy is difficult, often requiring multiple punctures to obtain a sufficient number of tissue samples. Several researchers have reported that endoscopic ultrasound elastography can differentiate benign from malignant pancreatic tumors and lymph nodes with high accuracy (Cui et al 2015; Iglesias-Garcia et al 2017). Despite these encouraging results, endoscopic ultrasound elastography is invasive and currently only available on one commercially available system, Hitachi’s EUB-8500 system.…”
Section: Introductionmentioning
confidence: 99%
“…There are different kinds of settings, where measurements can be done transdermally or in a trans-rectal endoscopic setting [53,58,90]. EUS elastography offers a high resolution of the digestive tract, close view of organs and lymph nodes [91,92]. Elastography techniques have been used in different ways in different studies; dynamic elastography shows promising results while SE has a lower cost, which makes this technique more accessible [73].…”
Section: Gastrointestinal Tractmentioning
confidence: 99%